Psoriasis, An inflammatory condition associated with oxidative stress - Pal, Swati; Sen, Sumit; Nath, Indrajit; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2021)
Background: Psoriasis is a chronic inflammatory skin disease characterized by pathological skin lesions due to various exogenous and endogenous factors. Oxidative stress can be one of the causes for the occurrence of psoriasis as well as significant contributor to its progression. Skin exposure to a number of irritants or proinflammatory agents including UVA and UVB generates ROS through the oxidative burst in infiltrating leukocytes at the site of inflammation which damages the skin cells. Measurement of the oxidative stress marker like lipid peroxidation product Malondialdehyde (MDA) and Nitric Oxide end products (NO2+NO3) along with the inflammatory marker hs-CRP in Psoriasis patients can uncover their role in disease causation, progression and development of various co-morbidities and timely prevention can significantly improve the quality of life of the psoriasis patients. Aims and Objectives: To measure the oxidative stress marker like lipid peroxidation product Malondialdehyde (MDA) and Nitric Oxide end products (NO2+NO3) along with the inflammatory marker hs-CRP in Psoriasis patients to uncover their role in disease causation, progression and development of various co-morbidities and timely prevention to significantly improve the quality of life of the psoriasis patients. Materials and Methods: Fifty patients of psoriasis mainly plaque type of either sex, in the age group of 35 ± 15.5 (range: 7-79) years were taken following inclusion and exclusion criteria. To evaluate the oxidative stress lipid peroxidation product malondialdehyde (MDA) and Nitric Oxide end products (NO2 + NO3) were measured. hs-CRP was measured as an inflammatory marker and their correlation with the disease severity and duration was evaluated. Results: A significant increase in malondialdehyde (MDA), Nitric Oxide end products (NOx) and hs-CRP levels (P<0.001) was noted in Psoriatic patients as compared to controls. There was a positive correlation between MDA, NOx and hs-CRP levels with the severity and duration of the disease. The correlation between hs-CRP and MDA and NOx also showed positive trend. Conclusion: Oxidative stress is one of the factors which can lead to the causation of Psoriasis and also significantly contribute to the disease progression and development of various co-morbidities. By measuring the oxidative stress marker and inflammatory marker in psoriasis patients early in the disease process we can employ preventive strategies for better management and improve the survival and quality of life.